Condition‐dependent movement and dispersal in experimental metacommunities. (24th July 2015) - Fronhofer, Emanuel A.; Klecka, Jan; Melián, Carlos J.; Altermatt, Florian; Navarrete, Sergio
Abstract Dispersal and the underlying movement behaviour are processes of pivotal importance for understanding and predicting metapopulation and metacommunity dynamics. Generally, dispersal decisions are condition‐dependent and rely on information in the broad sense, like the presence of conspecifics. However, studies on metacommunities that include interspecific interactions generally disregard condition‐dependence. Therefore, it remains unclear whether and how dispersal in metacommunities is condition‐dependent and whether rules derived from single‐species contexts can be scaled up to (meta)communities. Using experimental protist metacommunities, we show how dispersal and movement depend on and are adjusted by the strength of interspecific interactions. We found that the predicting movement and dispersal in metacommunities requires knowledge on behavioural responses to intra‐ and interspecific interaction strengths. Consequently, metacommunity dynamics inferred directly from single‐species metapopulations without taking interspecific interactions into account are likely flawed. Our work identifies the significance of condition‐dependence for understanding metacommunity dynamics, stability and the coexistence and distribution of species.